How Schools Can Promote Healthy Development for Newly Arrived Immigrant and Refugee Adolescents: Research Priorities. (February 2017) - McNeely, Clea A.; Morland, Lyn; Doty, S. Benjamin; Meschke, Laurie L.; Awad, Summer; Husain, Altaf; Nashwan, Ayat
ABSTRACT: BACKGROUND: The US education system must find creative and effective ways to foster the healthy development of the approximately 2 million newly arrived immigrant and refugee adolescents, many of whom contend with language barriers, limited prior education, trauma, and discrimination. We identify research priorities for promoting the school success of these youth. METHODS: The study used the 4‐phase priority‐setting method of the Child Health and Nutrition Research Initiative. In the final stage, 132 researchers, service providers, educators, and policymakers based in the United States were asked to rate the importance of 36 research options. RESULTS: The highest priority research options (range 1 to 5) were: evaluating newcomer programs (mean = 4.44, SD = 0.55), identifying how family and community stressors affect newly arrived immigrant and refugee adolescents' functioning in school (mean = 4.40, SD = 0.56), identifying teachers' major stressors in working with this population (mean = 4.36, SD = 0.72), and identifying how to engage immigrant and refugee families in their children's education (mean = 4.35, SD = 0.62). CONCLUSION: These research priorities emphasize the generation of practical knowledge that could translate to immediate, tangible benefits for schools. Funders, schools, and researchers can use these research priorities to guide research for the highest benefit of schools and the newly arrived immigrant and refugee adolescents they serve.